Coupling Stable Isotope Analysis with Gas Push‐Pull Tests to Derive In Situ Values for the Fractionation Factor αox Associated with the Microbial Oxidation of Methane in Soils. Issue 5 (31st August 2017) - Gebert, Julia; Streese-Kleeberg, Jan
Abstract : Core Ideas: Methane CH4 isotopologue fraction was measured in situ for the first time. αox varied strongly with oxidation rate. αox varied between landfills and between individual points on the same landfill. αox varied with spatial and temporal variability of soil properties. Our findings limit application of stable isotopes for CH4 oxidation quantification. A prerequisite for the application of stable isotope fractionation for the quantification of the methane (CH4 ) oxidation efficiency of landfill covers is that the fractionation factor αox is known or can be estimated with adequate accuracy. So far, αox has only been determined in laboratory experiments. In this study, αox was determined under in situ conditions in the field by coupling two independent methods, gas push‐pull tests and stable isotope analysis, to assess biological fractionation of CH4 isotopologues in landfill cover soils. On six landfills with nine points of investigation, 22 measurements were performed, covering a wide range of environmental conditions, such as soil temperature and moisture and observed oxidation rates. Values for αox varied between near 1, indicating little fractionation, and 1.151. Correlation of αox with the CH4 oxidation rate found by gas push‐pull tests revealed a clear asymptotic relationship, with low rates being associated with high values for αox and high rates resulting in little fractionation. Values for αox varied between the different landfills and between the individual points of investigation on the same landfill. The latter is assumed to reflect the spatial variability of methanotrophic activity due to spatial variability in soil moisture and hence air‐filled porosity as well as the spatial variability of gas fluxes. Significant variation of αox was observed for the same sampling point, presumably reflecting the temporal variability of factors influencing methanotrophic activity. These effects could include seasonally changing environmental conditions (e.g., soil temperature and moisture) but also the temporal variability of gas fluxes through the landfill soil cover, changing exposure of methanotrophs to CH4 and oxygen and hence their activity. The quantification of the CH4 oxidation efficiency using fractionation of stable isotopes is very sensitive to αox . Assuming a value constant in time and space and transferring this value from laboratory experiments to field settings entails significant uncertainty regarding the quantification of CH4 oxidation.